158k views
0 votes
Please help!!!!! And show all working out!!!

Please help!!!!! And show all working out!!!-example-1
User Mikus
by
6.7k points

1 Answer

2 votes

Answer:

y = x³ - 4x² + 27

Explanation:

given
(dy)/(dx) = 3x² - 8x , then

y = ∫(3x² - 8x) dx

integrate each term using the power rule

∫(a
x^(n)) =
(a)/(n+1)
x^(n+1) : n ≠ - 1

y = x³ - 4x² + c ( c is the constant of integration )

to find c substitute (- 2, 3) into the equation

3 = (- 2)³ - 4(- 2)² + c = - 8 - 16 + c ⇒ c = 27

y = x³ - 4x² + 27


User UnRewa
by
5.9k points